Enterprise Information Technology Strategic Plan in Delivering Indonesian Bank Performance Moderated by Bank Size - Wellianto Halim, Prof. Dr. Adler H. Manurung, Wibowo Kosasih, Firdaus Alamsjah (International Journal of Advanced Science and Technology, 2020)
Currently, most banking financial products and services apply information and communication technology (ICT) (nowadays called as digital technology (DT)) in the production and delivery process to enable the ineffective (doing right things) and efficient (doing things right) way to stay competitive. This research employs a purposive sample survey at the top 20 biggest asset in Indonesia banks, whose assets contribute to 72.5 % to total Indonesian banking industry, tested by qualitative and quantitative methodology using cross-section data and multiple regression analysis with Eviews 10 software from the primary survey data and the available secondary data in the market. The research result indicates the proper establishment processes of the enterprise information technology strategic plan (EITSP) significantly accommodating bank performance (BP = RoA) y. The data was moderated in accordance with bank size (BS) to provide optimal financial resources. The source of data from top Indonesian banks was planned as such institutions were leading source in the annual information technology strategic investment spending (ITIS), presenting agility and competitiveness.. However, the bank leaders’ competence (LC) and the bank leaders’ execution contribution (LEC) indicated insignificant result due to the technology standardized banking processes.Keywords: bank performance (RoA), bank size (BS), enterprise IT strategic plan (EITSP), leaders / senior management competence (LC) and Leaders Execution involvement/contribution (LEC), annual IT strategic investment spending (ITIS), Indonesian Banking Industry.